2020
DOI: 10.1093/ptep/ptaa012
|View full text |Cite
|
Sign up to set email alerts
|

Shell model results for nuclear β−-decay properties of sd-shell nuclei

Abstract: We evaluate the allowed β − -decay properties of nuclei with Z = 8 − 15 systematically under the framework of the nuclear shell model with the use of the valence space Hamiltonians derived from modern ab initio methods, such as in-medium similarity renormalization group and coupledcluster theory. For comparison we also show results obtained with fitted interaction derived from the chiral effective field theory and phenomenological USDB interaction. In this work, we have tested predictive power of ab initio eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Few noticeable mentions include shell model Monte Carlo technique (e.g., [? ]), thermal quasi-particle random-phase approximation, QRPA (e.g., [19][20][21]), large-scale shell model (e.g., [3]), Gross theory (e.g., [13]), density functional theory (e.g., [14]), Hartree-Fock-Bogoliubov method (e.g., [15]) and shell model (e.g., [16]).…”
Section: Of 17mentioning
confidence: 99%
See 1 more Smart Citation
“…Few noticeable mentions include shell model Monte Carlo technique (e.g., [? ]), thermal quasi-particle random-phase approximation, QRPA (e.g., [19][20][21]), large-scale shell model (e.g., [3]), Gross theory (e.g., [13]), density functional theory (e.g., [14]), Hartree-Fock-Bogoliubov method (e.g., [15]) and shell model (e.g., [16]).…”
Section: Of 17mentioning
confidence: 99%
“…Since the majority of these nuclei cannot be created under lab conditions, microscopic calculations of stellar weak-decay properties have gained importance in our quest to comprehend stellar processes. Numerous computations have focused on the mechanisms underlying stellar development and nucleosynthesis (e.g., [11][12][13][14][15][16]). Once an iron core develops in a giant star's later stages of evolution, there is no more fuel available to start a new burning cycle.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is the half-life method where the computed and experimental (partial) β-decay half-lives are matched by varying the value of g A . This method has been used for the allowed, forbidden, and two-neutrino double β decays in the framework of the proton-neutron quasiparticle random-phase approximation (pnQRPA) [7][8][9][10][11][12][13][14], the nuclear shell model (NSM) [15][16][17][18][19][20][21][22], and the interacting boson model (IBM) [23][24][25]. All these studies have shown that a quenched value of g A is needed in order to reproduced the experimental observations.…”
Section: Introductionmentioning
confidence: 99%
“…Study of nuclear structures up to Z = 20 and beyond using first principles or ab initio approaches has gained momentum over the past few years [32][33][34][35][36][37][38]. In Ref.…”
Section: Introductionmentioning
confidence: 99%